STUDY OF SCANDIUM ENRICHMENT IN NICKEL LATERITE TAPUNOPAKA AREA, NORTH KONAWE - Semedie, Tulus
Indonesia is the largest producer of nickel ore deposits in the world, spread across several regions in Indonesia, one of which is in Tapunopaka Village, North Konawe, Southeast Sulawesi. Nickel is one of the materials that is widely used for various industrial productions, so that the popularity of nickel continues to increase every year. The research area is located in Tapunopaka Village which is geologically included in the Ophiolite Complex in the form of ultramafic rocks. The physical and chemical weathering processes that occur in the bedrock produce nickel laterite deposits which are very well developed in the area. Several factors control the formation of laterite, namely factors of bedrock, climate, vegetation, structure, morphology and time. It belongs to the rock types of dunite and peridotite which are nickel-producing source rocks with a tropical climate. The vegetation is classified as dense with structures found in the form of fractures with a medium - high fracture intensity level which can facilitate the penetration of water into the rock. The morphology is classified as slope and steep with the laterite category on a well-developed slope morphology which is characterized by thick developed laterite. Meanwhile in the steep morphology, the laterite is not well developed which is characterized by thin laterite, but is spotted with good laterite in the presence of the mineral garnierite. Vertically, nickel laterite deposits are composed of topsoil, limonite, saprolite and bedrock zones. The enrichment zone for nickel (Ni) which is the main element in the laterite nickel exploration process is located in the saprolite zone. However, along with technological developments, the exploration process does not only focus on one element, but also other supporting elements, including Rare Earth Elements (REE). Scandium (Sc) is one of the rare earth elements which is widely used for modern industrial advancements, the battery industry, stainless coatings to sports equipment. Sc is concentrated from the weathering process of ultramafic rocks that are exposed to the surface due to tectonic activity and laterization processes. Sc is overflow in lateritic nickel deposits in limonite layers. The limonite zone is divided into two, namely red limonite and yellow limonite. Red limonite has a brownish red color which is composed of the minerals hematite and magnetite, which has undergone intensive weathering to the size of clay – silt grains. While yellow limonite has a reddish yellow to brownish yellow color which is composed of goethite minerals with material characteristics similar to red limonite. In the red limonite layer, the average Sc content is 73 ppm, which is sourced from 33 drill points. Meanwhile, the yellow limonite layer is divided into 2 parts based on the difference in high and low levels of Sc, namely top yellow limonite and bottom yellow limonite. The average grade of the top yellow limonite layer is 83 ppm, while the bottom yellow limonite layer has an average grade Sc is 67 ppm. Laboratory analysis was carried out in the form of petrographic analysis with 7 samples, Analysis Spectral Devices (ASD) with 11 samples, XRF analysis and ICP-MS analysis from 81 drill hole. The results of the petrographic analysis show that there are two types of lithological, namely dunite and harsburgite. Harsburgite with the dominant pyroxene mineral content has a greater Sc content compared to olivine dunite because there is a positive correlation between the Al element in pyroxene and the high scandium value. ASD analysis showed the presence of mineral oxides and alteration minerals including hematite, goethite, talc, montmorillonite, saponite and antigorite. Geochemical data shows a strong positive relationship between scandium and Al2O3 and Fe2O3 where the higher the levels of Al2O3 and Fe2O3 compounds, the higher the Sc content.